Didactic innovation with generative AI in university mathematics: experiences at TEC - Ramírez-Bogantes, Melvin (2026)
This article presents a set of didactic innovation experiences using generative artificial intelligence (GenAI) in university mathematics teaching at the Costa Rican Institute of Technology (TEC) during the 2024–2025 period. The initiative arises within the framework of the institution’s digital transformation and seeks to explore the pedagogical potential of GenAI as a cognitive and ethical mediator rather than as a substitute for human reasoning. The study adopts a descriptive qualitative approach with the direct participation of the teacher-authors, who implemented several experiences in mathematics courses. The results show that incorporating GenAI into the classroom can foster conceptual understanding, three-dimensional visualization, and digital literacy when integrated into activities with didactic design, pedagogical prompting, and systematic verification. Ethical and formative challenges were also identified, including superficial use, technological dependence, and the need to redesign assessment to value processes and explanations. From the perspective of the innovative teachers, GenAI is conceived as scaffolding for thinking and engaging in mathematical dialogue, promoting reflective teaching centered on the learner. In conclusion, the experience reaffirms that innovation does not reside in the technology itself but in the pedagogical purpose that guides it, and that GenAI contributes to developing reflection and critical thinking in university mathematics learning.